Induction of apoptosis and cell cycle arrest in two human cancer A549 and HT29 cells lines by Barhi date palm kernels extracts and three isolated cytotoxic compounds - Mahmud, Israa Ali; Mirghani, Mohamed Elwathig Saeed; Al-Qubaisi, Mothanna; , Beh Yee; Ismail, Norsharina; Rasedee, Abdullah; Yusof, Faridah; Shahabuddin, Munira; Al-khatib, Ma'an; Kabbashi, Nassereldeen Ahmed; Hashim, Yumi Zuhanis Has-Yun; Hilles, Ayah; et al. (MDPI, 2019)
Background and objectives: The initiation of apoptotic death in cancer cells is the aim of many chemotherapeutic strategies. As many anticancer agents have been discovered in natural plant sources, the search for novel phytochemicals displaying anticancer activities continues at a tremendous rate. This study was conducted to evaluate the effect of extractable polyphenols (EPP); non-extractable polyphenols (NEPP); nobiletin (NOB); tectorigenin (TEC) and persicogenin (PERS) from Barhi date palm kernels (BDPK) extracts on the induction of apoptosis in human lung cancer A549 and colon cancer HT29 cell lines. Materials and Methods: The anticancer activities were determined using MTT and trypan blue exclusion assays. Flow cytometry analysis was performed to study the cell viability, cell cycle arrest and apoptosis. The underlying mechanism of apoptosis induced by crude extracts and the purified compounds was investigated using caspase-3, -8 and -9 assays and the mitochondrial membrane potential assay. Results: The findings indicate that both BDPK extracts and the purified compounds do exert induced cell death on A549 and HT29 cells. The results observed from MTT- assay and trypan blue exclusion indicate that the cytotoxic effects of both plant extracts and the three isolated flavonoids are dose-dependent with higher cell death after 72 hours treatment. Treatment of human lung and colon cancer cells with EPP, NEPP, NOB, TEC and PERSI induced late stages of apoptosis as there was evidence of the DNA degradation and high percentage of the cells population was situated at sub-G1 phase, indicating a high population of apoptotic cells. Conclusions: Study of the apoptotic mechanism demonstrated that EPP and NEPP exhibited dependent mitochondrial signalling pathway as seen with caspase-9 and induced receptor-mediated (extrinsic) apoptotic pathway as seen with caspase-8. Therefore, our results suggest that BDPK extracts and the three isolated flavonoids could be a good candidate for developing anticancer agents.